Comparative study of Hg(ii) biosorption performance of xanthated and charred sugarcane bagasse from aqueous solutions. Issue 46 (19th October 2022) - Homagai, Puspa Lal; Bhattarai, Mahesh; Radhika, K. M.; Ghimire, Kedar Nath; Paudyal, Hari; Bhattarai, Ajaya
Abstract : Ion exchange adsorption mechanism of Hg(ii ) onto the monomeric unit of charred xanthated sugarcane bagasse (CXSB). Abstract : The main target of this study was to evaluate the efficiency of charred xanthated sugarcane bagasse (CXSB) and charred sugarcane bagasse (CSB) in the removal of Hg(ii ) ions from aqueous media. Batch experiments were performed to study the experimental parameters such as effects of pH, concentration, contact time and temperature. The adsorption velocity of Hg(ii ) onto CSB and CXSB was fast and reached equilibrium within 60 minutes. Isotherm and kinetic studies showed that Hg(ii ) uptake using both the biosorbents followed Langmuir isotherm and pseudo second order kinetics. The maximum adsorption capacity of Hg(ii ) at optimum pH 4.5 onto CSB and CXSB was found to be 125 mg g −1 and 333.34 mg g −1, respectively. A negative value of Δ G ° and positive Δ S ° value (0.24 kJ mol −1 for CSB and 0.18 kJ mol −1 for CXSB) for both the biosorbents confirm the spontaneous nature of Hg(ii ) adsorption. A positive value of Δ H ° (52.06 kJ mol −1 for CSB and 30.82 kJ mol −1 for CXSB) suggests the endothermic nature of biosorption. The investigated results shows that CXSB compared to CSB can be used as a low cost and environmentally benign bio-adsorbent for the removal of Hg(ii ) ions from aqueous solutions.